The Semiperipheral Subaltern and Literary Expression: Narratives from Turkey and India - DOĞANGÜN, SİMLA AYŞE (My University, 2023)
The onset of neoliberal capitalism has endowed the concept of “peripherality” with significant relevance for literary scholars investigating the dynamic interaction between aesthetic structures and the consequences of evolving socioeconomic and political terrains. Building on the theoretical foundations of subalternity, world-systems theory, and theories of combined and uneven development, I intend to present a comparative, constructive exploration of three distinguished novels from India and Turkey. These include Latife Tekin’s Berji Kristin: Tales from the Garbage Hills (Berji Kristin hereinafter), Arundhati Roy’s The God of Small Things (Small Things hereinafter), and Aravind Adiga’s The White Tiger (hereinafter White Tiger). My analysis delves into the intricate intertwining of familial dynamics, communal relations, gender violence, and patriarchal norms with the mechanisms of neoliberal market operations. In doing so, I strive to delineate the manner in which semiperipheral subalternity surfaces as a consistent theme of discourse within the distinct cultural landscapes of Turkey and India. Keywords: semiperiphery, India, Turkey, subaltern, world-system, neoliberalism
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; Karşılaştırmalı Edebiyat; Social Sciences and Humanities; Philology; Western Languages and Literatures; Comparative Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities; semiperiphery; India; Turkey; subaltern; world-system; neoliberalism